Violence in Argentine Literature and Film (1989-2005) - Garavelli, Clara (Imagofagia, 2021)
Sobre Rocha, Carolina y Elizabeth Montes Garcés (comps). Violence in Argentine Literature and Film (1989-2005). Canadá, University of Calgary Press, 2010, 251 pp., ISBN 978 1552385043. Palabras claves: reseña, Carolina Rocha, Elizabeth Montes, Violence in Argentine Literature and Film (1989-2005).